Investigating the Association between Social Factors and Life Satisfaction of High School Students - Dehghanpouri , Houriyhe; Mokaberian , Mansoureh (Shahroud Journal of Medical Sciences, 2021)
Background: Life satisfaction is one of the predictors of one’s psychological health which has attracted researchers’ attention. The study aimed to investigate the association between social factors and life satisfaction of high school students in Semnan Province, Iran. Methods: The statistical society of the research includes all high school students of Semnan Province, between the ages 12 to 17, in the 2019-2020 academic year. The number of students in this statistical society was 45834 students. The sample size of the statistical society was estimated as 381 students by the Cochran formula. In the present research, one of the limited probability sampling methods, that is multi-stage cluster sampling, was used. The tool used for data collection was a questionnaire. For answering the questions and analysis of the hypothesis, the Kruskal-Wallis test, Friedman correlation coefficient, and Regression analysis for answering the research questions and analysis of research hypothesis were used. The software used for data analysis was SPSS V25. The statistical significance was set at 0.05. Results: The findings of the research shows that there is a significant relationship between all social factors and the level of life satisfaction of high school students in Semnan province (P>value0.05). Conclusions: Considering the results of the study, it seems that life satisfaction among students is not made by a single cause; so different factors can bring about and improve such variables. Therefore, all capacities have to be used to create life satisfaction in high school students. Key Words: life satisfaction, Social factors, High school students.